Care-criminalisation: the involvement of children in out-of-home care in the New South Wales criminal justice system - McFarlane, Kathleen (The Australian and New Zealand journal of criminology, 2018)
This article discusses the involvement in the New South Wales criminal justice system of a cohort of children in out-of-home care. The paper reports the findings of a four-year research project that investigated the relationship between the child welfare and justice systems as experienced by a cohort of children in the New South Wales Children’s Court criminal jurisdiction. Analysis of 160 case files identified that children in out-of-home care appeared before the Children’s Court on criminal charges at disproportionate rates compared to children who were not in out-of-home care. The out-of-home care cohort had a different and negative experience of the justice system, entering it at a significantly younger age and being more likely to experience custodial remand, than children who had not been in out-of-home care. While both cohorts shared many of the risk factors common to young offenders appearing before the Children’s Court, the out-of-home care cohort experienced significant additional disadvantage within the care environment (‘care-criminalisation’), such that living arrangements designed to protect them from harm instead created the environment for offending. The paper concludes by arguing that a paucity of research exists regarding the drivers and dynamics of care-criminalisation and that more research is needed to explore the criminogenic impacts of a childhood spent in out-of-home care.